Information System Design Of Goods Stock Using Framework For The Application Of System Thinking (FAST) Method (Case Study CV. Aneka Mandiri Lestari) - Agarina, Melda; -, Sutedi (Prosiding International conference on Information Technology and Business (ICITB), 2017)
CV. Aneka Mandiri Lestari constitutes resulting company earth. Current stock management processes that are running in the CV. Aneka Mandiri Lestari is still done in a simple to use computer tool. However, systems that use has not been specifically designed for the purposes. Some data related to the management of the stocks on CV. Aneka Mandiri Lestari still organised and recorded using book so difficult in the process serving and reporting information associated. Information systems Design of goods stock It is a system that can handle the problem of inventory items, including the recording of incoming goods, against goods that come out, the purchase of raw materials, goods that are in the warehouse, and also reporting. This information system architecture using the FAST (Framework for the Application of System Technique) method. Based on the results of the functional testing, obtained that 100% of the system is valid. While the results from testing the usability, for the ease of use factor of 65% and activities of the experiment system based on scenario 85.5% of respondents strongly agree to ease of use this system. So from the test results it can be concluded that by using this stock information system can make CV Aneka Mandiri Lestari in the running of its business processes and systems that have been built can be received by users. To assist in processing stock items and sales generated a new system design, i/o design, database design and systems built using Visual Basic.Net The results of the data processing system of the manufacture and distribution of stock this stuff makes it easy for employees to entry, fix (edit), erase (delete), and search (searching) data reception and spending on goods, so as to facilitate in reporting revenue and expenditure itemsKeywords: goods stock, FAST